A Large-Scale, Low-Frequency Murchison Widefield Array Survey of Galactic H ii Regions between 260 < l < 340. (2016) - Hindson, L.; Johnston-Hollitt, M.; Hurley-Walker, N.; Callingham, J. R.; Su, H.; Morgan, J.; Bell, M.; Bernardi, G.; Bowman, J. D.; Briggs, F.; Cappallo, R. J.; Deshpande, A. A.; et al.
Abstract: We have compiled a catalogue of Hii regions detected with the Murchison Widefield Array between 72 and 231 MHz. The multiple frequency bands provided by the Murchison Widefield Array allow us identify the characteristic spectrum generated by the thermal Bremsstrahlung process in Hii regions. We detect 306 Hii regions between 260° < l < 340° and report on the positions, sizes, peak, integrated flux density, and spectral indices of these Hii regions. By identifying the point at which Hii regions transition from the optically thin to thick regime, we derive the physical properties including the electron density, ionised gas mass, and ionising photon flux, towards 61 Hii regions. This catalogue of Hii regions represents the most extensive and uniform low frequency survey of Hii regions in the Galaxy to date.